Description of a new species of Teratohyla Taylor (Amphibia: Athesphatanura: Centrolenidae) from north-western Ecuador - Cisneros-Heredia, Diego F.; Yánez-Muñoz, Mario H.; Ortega-Andrade, H. Mauricio (Zootaxa, 2009)
We describe a new species of Glassfrog of the family Centrolenidae. This new taxon, Terarohyla sornozai sp. nov., is diagnosed by having a protruding snout in lateral profile, uniform green dorsal colouration in life, concealed prepollex, extensive webbing between the outer fingers, fully webbed toes, and small body size. It inhabits the Non-Seasonal Evergreen Foothill and Lowland forests in the provinces of Esmeraldas, Imbabura, and Pichincha, north-western Ecuador.